Pendampingan Wali Murid Melalui Parenting Islami Di Masa Pandemi Covid-19 - Bambang Wahrudin; Wawan Kusnawan; Rohmadi Rohmadi (AL-ASASIYYA: Journal Of Basic Education, 2021)
The COVID-19 pandemic has not yet ended, its existence has directly changed human traditions and culture. The education sector has also been affected by this pandemic. At least in the 2020/2021 academic year, educational institutions in Indonesia in particular cannot carry out face-to-face learning processes in schools as usual. Learning is carried out online or online, this results in the learning process for elementary age children (MI) being very dependent on their parents. The condition of parents and teachers of MI Muhammadiyah 6 Nglegok Ponorogo students is very varied, some do not have online communication tools (do not have cellphones/computers), some are busy working, some are unable to meet their daily quota and some complain because they are no longer able to accompany them. children learn. Departing from these problems, we were moved to contribute to helping MI Muhammadiyah 6 Nglegok Ponorogo to provide solutions by assisting guardians so that they can follow the learning that has been set by the madrasa. The mentoring program for student guardians during the pandemic through Islamic parenting is an alternative that can be implemented at MI Muhammadiyah 6 Nglegok Ponorogo considering that the school is currently implementing the adab and al-Qur'an school program which makes adab in Islamic teachings and tahfidz al-Qur'an education as a program. main madrasa. The task of educating teachers at school should be carried out at home, this requires good communication and cooperation between teachers at school and parents at home so that educational goals can be achieved. Islamic parenting that is carried out provides great benefits because as a medium of communication and coordination between the madrasa and the home, Islamic parenting also provides opportunities for counseling so that it can provide solutions for parents while accompanying children to study at home. From Islamic parenting and counseling that has been carried out, many problems have been inventoried by madrasas so that they become material for consideration for educational programs in the future. The solution to the guardian's problem can be resolved during parenting and there are also those who require follow-up assistance.